2015
DOI: 10.1371/journal.pone.0139350
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Toll-Like Receptors 2 and 4 Prevents Renal Ischemia-Reperfusion-Induced Cardiac Hypertrophy in Mice

Abstract: We investigated whether the pathways linked to Toll-like receptors 2 and 4 (TLRs) are involved in renal ischemia-reperfusion (I/R)-induced cardiac hypertrophy. Wild type (WT) C57BL/6J, TLR2-/- and TLR4-/- mice were subjected to left kidney ischemia for 60 min followed by reperfusion for 5, 8, 12 and 15 days. Proton density magnetic resonance showed alterations in the injured kidney from WT mice, together with signs of parenchymal edema and higher levels of vimentin mRNA, accompanied by: (i) small, but signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
70
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 63 publications
12
70
1
Order By: Relevance
“…Interestingly, a previous study revealed that SHP-2 suppressed the expression of TLR3-activated pro-inflammatory cytokine IL-6 and TNF-α, and the silencing of SHP-2 increased the expression of TANK binding kinaseactivated IFN-b and TNF-α [30]. The absence or inhibition of TLRs suppresses cardiac hypertrophy induced by I/R, whereas TLR2 and TLR4 have been shown to mediate systemic inflammatory responses and NF-κB activation [31]. Moreover, inflammation is a key factor in the occurrence and development of ischemic damage, which is secondary to an intense inflammatory response [32].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, a previous study revealed that SHP-2 suppressed the expression of TLR3-activated pro-inflammatory cytokine IL-6 and TNF-α, and the silencing of SHP-2 increased the expression of TANK binding kinaseactivated IFN-b and TNF-α [30]. The absence or inhibition of TLRs suppresses cardiac hypertrophy induced by I/R, whereas TLR2 and TLR4 have been shown to mediate systemic inflammatory responses and NF-κB activation [31]. Moreover, inflammation is a key factor in the occurrence and development of ischemic damage, which is secondary to an intense inflammatory response [32].…”
Section: Discussionmentioning
confidence: 97%
“…By combining analysis of immunoblot, ELISA and IHC of the same samples, we obtained convincing evidence that I/R‐associated cytoplasmic translocation and extracellular release of HMGB1 can be completely inhibited by either pre‐I/R or delayed FGF2 treatment. As circulating HMGB1 is known to activate proinflammatory signalling pathways through its interaction with pattern recognition receptors such as TLR2 and TLR4; both of which are crucial pro‐inflammatory factors in exacerbating I/RI as demonstrated using their respective knockout mouse models . We therefore further measured the mRNA expression of TLR2 and TLR4 in the kidneys, and confirmed that I/RI significantly induced TLR2 expression, which is completely obliterated upon FGF2 treatment.…”
Section: Discussionmentioning
confidence: 57%
“…[31,32] NF-jB and MAPK pathways are proved to be important in the pathogenesis of cerebral ischaemia. [33] TLR5 can constitute as dimerization to activate NF-jB. Several evidences confirmed that the inhibition of TLR4 could protect against ischaemic brain damage and injury in rats.…”
Section: Discussionmentioning
confidence: 95%
“…The recruitment of the myeloid differentiation primary response protein 88 (MyD88) subsequently facilitates the activation of downstream signalling pathways like the NF‐κB and MAPK pathways by activating TLR4/CD14 . NF‐κB and MAPK pathways are proved to be important in the pathogenesis of cerebral ischaemia . TLR5 can constitute as dimerization to activate NF‐κB.…”
Section: Discussionmentioning
confidence: 99%